Update on primary ciliary dyskinesia. Issue 7 (July 2017) - Robson, Evie Alexandra; Chetcuti, Philip; Hirst, Robert Anthony; Mitchison, Hannah; Moya, Eduardo; Peckham, Daniel; Robinson, Philip J.; Rutman, Andrew; O'Callaghan, Christopher
Abstract: PCD is a rare autosomal recessive disorder of ciliary function. It is characterised by progressive sino-pulmonary disease, fertility problems and disorders of organ laterality. Clinical phenotype and disease course can vary significantly. A daily chronic wet cough that never goes away is invariably present, with most suffering from persistent and significant rhinosinusitis. Middle ear effusion and hearing difficulty are seen in a proportion of patients. Bronchiectasis is reported in approximately 70% of children. Diagnosis can be difficult and often requires specialist centre input. In patients with a suggestive clinical phenotype a combination of nasal nitric oxide, high-speed video microscopy analysis for ciliary beat frequency and pattern, and transmission electron microscopy analysis of ciliary ultrastructure are performed as appropriate. In populations studied genetic defects have been identified in approximately 60% of cases, with many genes yet to be discovered. There is no evidence on which to base guidelines of clinical management and most treatment regimens are extrapolated from those used in Cystic Fibrosis. Specialist care by respiratory and ENT specialists is recommended. Current respiratory management focuses on physiotherapy and exercise to help compensate for defective mucociliary transport together with identification and treatment of infection. Ongoing international collaboration is key in being able to better understand a disease of such heterogeneity and to produce best practice guidance for standardised clinical care.